Nexus between organizational citizenship behavior and psychological wellbeing: emotional intelligence as a pathway - Prasad, KDV; Singh, Shivoham; Srinivas, Ved; Vaidya, Rajesh; Dave, Krishna Kant (Frontiers in Psychology, 2024)
Aim/purpose The aim of this study is to investigate the nexus between organizational citizenship behavior and psychological wellbeing and assess the moderating and mediating effects of emotional intelligence (EI) on the relationship betwem psychological wellbeing of IT-enabled Sector employees in Hyderabad. Design/methodology/approach To measure the study variables of organizational citizenship behavior (OCB) and emotional intelligence (EI) on psychological wellbeing (PWB) data were gathered using a questionnaire. The mediating and moderating effects of emotional intelligence on the relationship between organizational citizenship behavior and psychological wellbeing was also assessed. The was reliable as indicated by the Cronbach's alpha coefficient statistic that between 0.79 to 0.91. Findings Three hundred valid responses were considered for SEM analysis using AMOS, version 28. The model fit indices indicate excellent fit: CMIN/DF 2.788 CFI 0.935, IFI 0.937, TLI 0.921, NFI 0.923, RMSEA 0.054, SRMR 0.077 and PClose 0.092. The SEM analysis revealed that the impact of exogenous variables OCB and EI were statistically significant (p < 0.001) on endogenous variable psychological wellbeing of IT-enabled industry employees. Furthermore, EI partially mediates psychological wellbeing through the OCB of information technology employees. This empirical study also examined the moderating effects of EI on the psychological wellbeing of information technology-enabled employees through OCB. The slope analysis reveals that emotional intelligence strengthens the positive association between OCB and the PWB of IT-enabled sector employees. EI and OCB enhance PWB and employee performance. Research implications/limitations The findings of this study have several important implications for organizations in the IT sector and can be used to develop strategies for promoting OCB and EI among employees. The structural relationships between PWB and OCB in the context of hotel employees and reported positive effects of OCB on hotel employees are well documented. The limitations are the data were collected from the Information Technology employees of Hyderabad Metro. There are some subjectivity and cultural issues which were elaborated at the end Contribution/Originality This empirical study helps to clarify the relationship between organizational citizenship behavior, psychological wellbeing, and the mediator and moderator variable emotional intelligence. The study also comprehends the available literature and adds value to the existing theoretical knowledge and behavioral studies. JEL classification M10 M12, M19.